Entre la parole et l’image : le système mythopoétique marubo - Pedro de Niemeyer Cesarino (Journal de la Société des Américanistes)
Between the verbal and the visual: Marubo mythopoetic system. The verbal arts of the Marubo (a Panoan-speaking people from Vale do Javari, Amazonas, Brazil) are systematically connected with iconographic productions and with certain ritual configurations, which seem to indicate the conditions of a visual thought. The study of poetic formulas reveals a previous structural scheme that can be transposed to graphic signs and choreographic configurations. The shamans instantiate a virtual formulaic system by manipulating three of the verbal art modes according to specific ends. Chanted mythical narratives (saiti), curing chants (shõki) and spirit chants (iniki) are articulated in certain uses of the poetic formulae, related to the personified socio-cosmic field. The transformation and composition relationships of the previous schemes constitute a specialized mythological and poetic knowledge, characterized by transmission and acquisition processes that are connected to the exo-centered Amerindian cosmologies.